The influence of the beliefs of Italian and Spanish managers in their engagement in sustainability reporting - Juan J. García-Machado; Marco Papa; Mario Carrassi (Discover Sustainability, 2023)
Abstract The EU legislature, through the approval of the Non-financial Information Directive, has made a decisive step towards a mandatory regime for Sustainability Reporting as an essential condition to promote sustainable behavior across European countries. This paper aims at examing the impact of managers’ beliefs and attitudes on NFI mandatory reporting practices through the Theory of Planned Behavior. We test whether managers’ attitudes, subjective norms, and perceived behavioral control impact the quality of sustainability reports in Spain and Italy. We built a reflective-formative hierarchical component PLS-SEM model, tested in a survey of 104 Italian (56.73%) and Spanish (43.27%) managers, that combines different latent variables and their relationships, which confirms all our hypotheses. This cross-country analysis is motivated by some differences between Italy and Spain in their cultural orientation and in the area non-financial reporting. To measure Non-financial Information, we crafted a Sustainability Reporting Quality Index for the same companies of the surveyed managers, that combines several reporting features of disclosure quality. We also consider whether other external factors, such as governance characteristics, social influence, and sustainable education, affect managers’ intention to engage in Sustainability Reporting. The results reveal that our model, along with sustainable education and social influence explain more than 56% of the intention to engage in Sustainability Reporting. This indicates that the latter latent variable is well predicted, confirming the relevance of managers’ beliefs in driving quality Sustainability Reporting practices. Our findings may specifically help business managers and decision-makers to identify the factors that are likely to influence sustainability reporting in Italy and Spain and contribute to develop efficient sustainable reporting strategies by decision-makers.